Building responsive and responsible financial regulators in the aftermath of the global financial crisis - Iglesias-Rodríguez, Pablo (Intersentia, 2015)
The global financial crisis that started in 2007 sparked several academic debates about the role that financial sector regulators played in the crisis and prompted policy reforms in the financial supervision architectures of several countries. This book focuses on the question of what accountability, independence, transparency and, more generally, governance mechanisms applicable to financial regulators can better contribute to building responsive, responsible and effective regulatory and supervisory frameworks that tackle the weaknesses of the pre-crisis regimes. It re-visits the concepts of accountability and independence of financial regulators as well as the main economic theories underlying financial services policy-making, in light of the crisis experience